Redox-Hopping-Based Charge Transport Mediated by Ru(II)-Polypyridyl Species Immobilized in a Mesoporous Metal-Organic Framework - Duan, Jiaxin; Goswami, Subhadip; Hupp, Joseph T. (Frontiers in Chemical Engineering, 2022)
Electronic charge-transport through crystalline metal-organic frameworks (MOFs), can be accomplished by site-to-site electron (or hole) hopping, provided redox-active sites, such as easily reducible or oxidizable MOF linkers, are present. If the framework itself is redox-inert, solvent-assisted ligand incorporation (SALI) of redox-active moieties can serve to enable hopping-based charge transport. Here, we have studied redox-hopping process within Ru-bpy@NU-1008, where Ru-bpy is a carboxylate-functionalized derivative, i.e. a node-ligating derivative, of the well-known chromophore, Ru(2,2’-bipyridine)32+ and NU-1008 is a redox-inert MOF featuring hierarchical porosity and csq topology. Chronoamperometry experiments with on electrode-supported thin films of Ru-bpy@NU-1008 show charge-transport is feasible throughout the MOF, with the transport being diffusion-like and with the magnitude of the apparent diffusion-coefficient for redox-hopping-based transport being 6 × 10-12 cm2/s.